Executive Summary on Combating COVID-19: A Perspectives and Challenges from Nigerian Nurses - Grace Ogiehor-Enoma; Dorothy C. Nwanonyiri; Emilia Iwu; Ednah N. Madu; Assumpta Ekeh; Ruth Ifediora; Margaret Okodua (New Horizons in Medicine and Medical Research Vol. 10, 2022)
With the declaration of Coronavirus Disease 2019 (COVID-19) as a Public Health Emergency of International Concern (PHEIC) on January 30, 2020 and the incredible speed at which the virus changed around the world, countries employed various strategies to reduce the transmission. In addition to personal preventive measures (e. g. hand hygiene, respiratory etiquette, face covers, and environmental disinfection), transmission reduction strategies including social/physical distancing, stay-at-home orders, schools, and nonessential business closure, bans on public gatherings, travel restriction, aggressive case identification, isolation, contact tracing and vaccination programs were employed. Before the outbreak originated in Wuhan, China on December 2019, there was no information about the virus. However, as the entire world battled the virus, nurses continue to provide care, comfort, and information to patients at all levels while risking their personal safety and well-being. This executive report provides an insight to Nigerian nurses’ perspectives and challenges in combating COVID-19 and the role the National Association of Nigerian Nurses in North America (NANNNA) played in supporting nurses during the surge through various programs including vaccination program. Capturing nursing practice and nurses’ experiences during COVID-19 surge provide real-time guidance to mitigating challenges and improving well-being of nurses during pandemic.